Pengaruh Pemahaman Peraturan Pajak, Tarif Pajak, Lingkungan, dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Pada UMKM - Ratih Kumala; Ahmad Junaidi (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2020)
One of the tax receipts received by the state is used to finance development in Indonesia. For development to run smoothly, the revenue received by the state must increase. The large number of taxpayers will affect the increase in revenue sources because the more the number of compliant taxpayers, the more the source of state income. However, an active role, tax rates, environmental taxpayers, and taxpayer awareness are needed in this regard. This study aims to examine the effect of understanding tax regulations, tax rates, the environment, and taxpayer awareness of taxpayer compliance in Micro, Small and Medium Enterprises (MSMEs). This research method uses quantitative descriptive methods. The population of this study is the MSMEs taxpayer who has been operating for at least one year and has a gross circulation not exceeding 4.8 billion rupiahs in one tax year, because this is based on the provisions of PP No. 23 of 2018. The research sample used simple random sampling technique. The data used are primary data taken based on questionnaires distributed by 100 respondents. The results of this study indicate that the variable understanding of tax regulations significantly influence the compliance of MSMEs taxpayers. Then the variable tax rates, environmental taxpayers and taxpayer awareness do not have a significant effect on tax compliance of MSMEs